Translation and the Circulation of Competing Narratives from the Wars in Chechnya: A Case Study from the 2004 Beslan Hostage Disaster - Harding, Sue-Ann (Meta, 2011)
This paper examines Russian and English reportage published online over the course of Wednesday, 1 September, the first day of the three-day hostage-crisis that took place in Beslan, Southern Russia in 2004. The material selected for analysis comes from three disparate news agencies: RIA-Novosti, a major, state-controlled Russian news agency; Kavkazcenter, the website of the Chechen armed resistance; and Caucasian Knot, a site founded by Memorial, Russia’s international and historical human rights society. Drawing on tenets of socio-narrative theory that combine narratological tools with the idea of ‘ontological narrativity’ (Somers and Gibson 1994: 38), the paper analyses the construction of the news narratives published by each website, before turning to a comparative analysis of the translated material also published that day. The paper thus contributes to academic knowledge regarding the Beslan hostage-taking and the discourses generated by the event – particularly those produced by fringe groups and in translation – as well as to knowledge of narrative construction as events are still occurring. Preliminary conclusions are drawn regarding the effect of translation on these competing narratives, particularly those circulated by opposition, non-mainstream groups concerning situations of violent political conflict, such as that which still continues in Chechnya and the North Caucasus.